Comparative study of efficacy of femoral nerve block and IV fentanyl for positioning during femur fracture surgery - Reddy, E. Devendar; Rao, B. Dinakar (International Surgery Journal, 2016)
Background: Spinal anesthesia is the preferred technique for femoral fracture surgeries. Since there is a very low threshold of pain in this area, intravenous fentanyl and femoral nerve blockers are generally administered to relieve the pain during the positioning of the hip before surgery. This study was performed to compare the efficacy of femoral nerve block over fentanyl. Methods: 72 patients between the ages of 18 – 70, who had femur fracture and unable to sit due to extreme pain were included into the study. The patients were divided into 2 groups based on the random number table, to receive Femoral Nerve Block (FNB group) and intravenous fentanyl (IVF group). Vital statistics, visual analog scale for pain measurement and patient satisfaction was noted. Results: The VAS scores 15 mins after analgesic in FNB group were 3.1 ± 2.1 compared to 3.9 ± 1.9 in IVF group and during the positioning, 6.2 ± 2.1 and 7.2 ± 2.7 respectively. Time to perform surgery was 2.0 mins ± 1.9 in FNB group and 3.6 ± 1.4 in IVF group while patient satisfaction was 32 and 26 respectively in the FNB and UVF groups. Conclusions: Our study revealed that femoral nerve block was a better analgesic drug compared to intravenous fentanyl for positioning of the hip during spinal anesthesia in femoral fracture surgeries.